1991
DOI: 10.1111/j.1502-3931.1991.tb01491.x
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecules in brachiopod shells: characterization and diagenesis

Abstract: An immunological investigation was conducted of soluble intra‐crystalline macromolecules isolated from living and fossil brachiopod shells, which had previously been used for an immunologically based study of phylogeny (serotaxonomy). The soluble intra‐crystalline macromolecules comprised 0.03% by weight of the extant shell material. Bulk analysis and gel electrophoresis indicated that the organic material is predominantly glycoprotein, and contains up to 30% by weight carbohydrate. Treatment of the macromolec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…However, remains of organic matrices within the older skeletal parts can sometimes be still preserved, as shown by the very rare occurrence of the amide I band in some spectra of Leptastraea and the quite common presence of carbon measured in the calcification centers of Lobophyllia. Several previous works deal with degradation of soluble intraskeletal organic matrices extracted from fossil carbonate skeletons, including mollusks, brachiopods, corals, and sponges from various ages (Ivanov et al 1972;van der Meide et al 1980;Collins et al 1991;Gautret and Marin 1993;Gautret and Aubert 1993;Gautret 2001). Although involving different time spans, these studies have shown a gradational decrease of the amount of soluble intraskeletal matrices which can be extracted from fossils of increasing ages by comparison with their living counterparts.…”
Section: Differential Diagenetic History Of Organic and Mineral Compomentioning
confidence: 98%
“…However, remains of organic matrices within the older skeletal parts can sometimes be still preserved, as shown by the very rare occurrence of the amide I band in some spectra of Leptastraea and the quite common presence of carbon measured in the calcification centers of Lobophyllia. Several previous works deal with degradation of soluble intraskeletal organic matrices extracted from fossil carbonate skeletons, including mollusks, brachiopods, corals, and sponges from various ages (Ivanov et al 1972;van der Meide et al 1980;Collins et al 1991;Gautret and Marin 1993;Gautret and Aubert 1993;Gautret 2001). Although involving different time spans, these studies have shown a gradational decrease of the amount of soluble intraskeletal matrices which can be extracted from fossils of increasing ages by comparison with their living counterparts.…”
Section: Differential Diagenetic History Of Organic and Mineral Compomentioning
confidence: 98%
“…[30] Caramelization, well known in cooking, involves anhydrous reactions between sugars and amino acids in Maillard-type condensations to form melanoidin compounds. Melanoidins have been reported in fossil molluscs and brachiopods [69,70] and are important in the formation of humic acids and kerogens. [71] The reaction of proteins with saccharides to form melanoidin www.advancedsciencenews.com www.bioessays-journal.com complexes may also explain the preservation of skin in human bog bodies.…”
Section: The Molecular Composition Of Tissues and Their Decay Environmentioning
confidence: 99%
“…Compositional differences between sediment size and density fractions are well known [77,79,80], but more work is needed in order to characterize the relative lability of specific organic substances associated with these different fractions. Organic matter that is incorporated into silicate and carbonate tests during biological deposition of these minerals is better preserved than cellular organic matter: mineral-bound amino acids are well protected from diagenesis and remain relatively unaltered chemically [86,87] compared to cellular amino acids. In a study of opal-rich Southern Ocean sediments, Ingalls et al [88] showed that the proportion of silica-bound amino acids increased significantly with increasing depth in the sediments, reaching > 50% of total hydrolyzable amino 4 Correlation between mineral surface area and total organic carbon content of marine sediments collected from a the Washington continental margin and b the California continental margin.…”
Section: Matrix Effectsmentioning
confidence: 99%